Postoperative ctDNA detection predicts relapse but has limited effects in guiding adjuvant therapy in resectable stage I NSCLC - Wang, Bolin; Zou, Bing; Xu, Shengnan; Zhao, Chao; Pei, Jinli; Wang, Shijie; Zhao, Kunlong; Yu, Jinming; Liu, Jie (Frontiers in Oncology, 2023)
Background: To date, identifying resectable stage I non-small cell lung cancer (NSCLC) patients likely to benefit from adjuvant therapy (ADT) remains a major challenge. Previous studies suggest that circulating tumour DNA (ctDNA) is emerging as a promising biomarker for NSCLC. However, the effectiveness of ctDNA detection in guiding ADT for resectable stage I NSCLC patients remains elusive. This study aimed to elucidate the role of ctDNA detection in estimating prognosis and guiding ADT for resectable stage I NSCLC patients. Methods: Individual patient data and ctDNA results data were collected from 270 patients across four independent cohorts. The detection of ctDNA was conducted at 3 days to 1 month after surgery. The endpoint for this study was relapse-free survival (RFS) and overall survival (OS). Results: Of the 270 resectable stage I NSCLC patients, 9 patients with ctDNA-positive and 261 patients with ctDNA-negative. We found that the risk of recurrence was significantly lower in the ctDNA-negative group compared to the ctDNA-positive group(HR=0.11, p＜0.0001). However, there is no difference in the risk of death between the two groups (p =0.39). In the ctDNA-positive group, there were no significant differences in RFS between patients who received ADT and patients who did not receive ADT (p =0.58). In the ctDNA-negative group, those who received ADT had a worse RFS in comparison with those who did not receive ADT (HR=2.36, p =0.029). No difference in OS was seen between patients who received ADT and patients who did not receive ADT in both the ctDNA-positive group and the ctDNA-negative group (All p values＞0.05). Furthermore, there was no difference in RFS and OS between patients who received chemotherapy-based or tyrosine kinase inhibitor-based ADT and patients who did not receive ADT in both the ctDNA-positive group and the ctDNA-negative group (All p values＞0.05). Conclusions: Postoperative ctDNA detection can be a prognostic marker to predict recurrence but has limited effects in guiding ADT for resectable stage I NSCLC. Future prospective investigations are needed to verify these results.